Dinamika Konstruksi Makna Pembelajaran Hadis di Era Digital: Kajian Deskriptif pada Mahasantri Ma’had Aly Tebuireng Jombang - Moh Misbakhul Khoir; Abdur Ro'uf Hasbullah; Try Heni Aprilia (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2026)
ABSTRACT Digital transformation has altered hadith learning practices in pesantren. This study analyzes the dynamics of meaning construction of hadith learning in the digital era among students of Ma’had Aly Hasyim Asy’ari Tebuireng Jombang using Symbolic Interactionism. Employing a qualitative case study, data were collected through 2 months of participant observation, in-depth interviews with 12 students and 3 lecturers, and documentation. The findings reveal that digital technology does not replace traditional authority but is negotiated hierarchically. Turāth books, sanad, and the kiai figure remain the primary significant symbols of scholarship. Digital media such as apps and the internet are interpreted as secondary instrumental symbols whose legitimacy depends on lecturer guidance. Three processes were identified: 1) critical selection of digital source validity, 2) mediation by kiai/lecturer authority, and 3) technological adaptation within pesantren ethics. The novelty lies in mapping meaning construction from the pesantren actors’ perspective, showing that digital transformation is adaptive rather than disruptive. This contributes to contemporary hadith studies and pesantren education discourse. Keywords : Symbolic Interactionism; Ma'had Aly; Hadith Learning; Digital Transformation; Scholarly Authority.